Learning to imitate individual finger movements by the human neonate. Issue 6 (23rd April 2014) - Nagy, Emese; Pal, Attila; Orvos, Hajnalka
Abstract Imitation in human neonates, unlike imitation in young infants, is still regarded as controversial. Four studies with 203 newborns are presented to examine the imitation of index finger, two‐ and three‐finger movements in human neonates. Results found differential imitations of all three modelled gestures, a left‐handed pattern, and a rapid learning mechanism. The lateralized behavioural pattern suggests the involvement of a right lateralized neural network, and the mechanisms described in this study – (i) the accurate imitation of all aspects of the model's movements, (ii) the rapid learning component, and the (iii) the early sensitive period might fulfil the criteria for filial imprinting.